2004
DOI: 10.1016/j.ydbio.2004.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the developing Drosophila CNS midline cells

Abstract: The Drosophila CNS midline cells constitute a specialized set of interneurons, motorneurons, and glia. The utility of the CNS midline cells as a neurogenomic system to study CNS development derives from the ability to easily identify CNS midline-expressed genes. For this study, we used a variety of sources to identify 281 putative midline-expressed genes, including enhancer trap lines, microarray data, published accounts, and the Berkeley Drosophila Genome Project (BDGP) gene expression data. For each gene, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 77 publications
5
110
1
1
Order By: Relevance
“…Acf1 contains two PHD fingers and a bromodomain, and it associates with Imitation of Switch (ISWI), a homolog of yeast SWI2/SNF2 and a small subunit of ACF (22,23). The expression of Acf1 was observed in a subset of cells in the midline primordium region of the CNS (24). Embryos injected with Acf1 dsRNA exhibited missing segments (Fig.…”
Section: Genes With Previously Uncharacterized Nervous System Phenotymentioning
confidence: 99%
“…Acf1 contains two PHD fingers and a bromodomain, and it associates with Imitation of Switch (ISWI), a homolog of yeast SWI2/SNF2 and a small subunit of ACF (22,23). The expression of Acf1 was observed in a subset of cells in the midline primordium region of the CNS (24). Embryos injected with Acf1 dsRNA exhibited missing segments (Fig.…”
Section: Genes With Previously Uncharacterized Nervous System Phenotymentioning
confidence: 99%
“…Embryo collection, in situ hybridization, immunostaining and confocal imaging were performed as previously described (Kearney et al, 2004;Wheeler et al, 2006;Wheeler et al, 2008). Digoxygenin-labeled or biotinlabeled antisense RNA probes for 5-HT1A, BarH1, CG13565, CG15236, CG16778, DAT, dgk, Glu-RI, NPFR1, nubbin, ple, pdm2, Tbh, wor, wrapper and VGlut for in situ hybridization were generated from cDNA clones from the Drosophila Gene Collection (Open Biosystems).…”
Section: In Situ Hybridization Immunostaining Microscopy and Statimentioning
confidence: 99%
“…The proneural bHLH genes play important roles in CNS and sensory cell development (Bertrand et al, 2002). Previous work has shown that l(1)sc was expressed in midline cells (Bossing and Brand, 2006;Kearney et al, 2004) and we earlier described the expression of ase in MPs and MNB (Wheeler et al, 2006). However, detailed expression analysis of the ac, l(1)sc and sc genes had not been carried out.…”
Section: As-c Genes Are Expressed In Midline Precursors and Their Neumentioning
confidence: 99%
“…The gene was named mes2, based on its expression in the early mesoderm, and we shall henceforth refer to it by this name. mes2 has since been identified in several additional microarraybased screens that examined transcript levels in the wing imaginal disc (Butler et al, 2003), glia (Freeman et al, 2003), and the central nervous system (CNS) midline (Kearney et al, 2004).…”
Section: Resultsmentioning
confidence: 99%